2018
DOI: 10.1093/icvts/ivy187
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical characterization and comparison of different aortic root surgical techniques

Abstract: In conclusion, the David procedure may stabilize the aortic annulus more than the Yacoub procedure, whereas the leaflet opening area was larger in the latter (P = 0.030). No difference (P = 0.309) was found in valve-opening delay between groups. The 2 interventions show similar characteristics at the sinotubular junction, whereas the David technique seemed more restrictive at the annular level than the Yacoub technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“… 3 Some studies have suggested that the remodeling technique, which also spares the shape of the sinuses of Valsalva, results in more natural aortic root biomechanics. 4 , 5 However, reimplantation of the aortic valve addresses annular dilation and externally supports any remaining abnormal valvular tissue, and in some series, demonstrates greater long-term durability. 6 8 …”
mentioning
confidence: 99%
“… 3 Some studies have suggested that the remodeling technique, which also spares the shape of the sinuses of Valsalva, results in more natural aortic root biomechanics. 4 , 5 However, reimplantation of the aortic valve addresses annular dilation and externally supports any remaining abnormal valvular tissue, and in some series, demonstrates greater long-term durability. 6 8 …”
mentioning
confidence: 99%
“…Various surgical techniques have been used to repair a dilated aortic root [ 9 13 ], all aiming at finding the ideal method to stabilize the aortic root in an effective and durable manner, as well as reestablishing biomechanical properties similar to the native aortic root [ 13 , 14 ]. It has previously been shown that a flexible aortic root is essential for the natural physiological movement of the aortic valve leaflets and the aortic annulus [ 15 ].…”
Section: Introductionmentioning
confidence: 99%